Development, validation, and evaluation of the systematic assessment for resilience framework - Wadi, Majed Mohammed Saleh (2023)
Mental health issues, such as stress, anxiety, burnout, and depression, continue to rise among medical students, resulting in negative side effects that ultimately jeopardize optimal medical care and patient health. Evidence indicates that assessment is the primary cause of these mental issues. Although several interventions have been initiated to improve the mental health of medical students, these have focused on individual aspects, ignoring a comprehensive approach across multiple levels and the assessment itself as the root cause. The emerging resilience intervention has an advantage over other mental health interventions, which has led researchers begin to implement it. The purpose of this study was to develop, validate, and evaluate a systematic framework for promoting resilience through the assessment system. In the first phase, four narrative reviews, a scoping review, and a focus group discussion were conducted to lay a solid foundation for the framework’s development. The second phase involved content validation and the response process (face validation). The new framework was evaluated in the third and final phase using two tracks: first, by training a group of international medical teachers and measuring their utilization of the framework’s guidelines before and after training and, second, by implementing the framework in a single medical institution and measuring certain mental health parameters among medical students before and after the training of their medical teachers to apply the framework. Furthermore, qualitative feedback was gathered for both evaluation tracks. After synthesis and triangulation of the results gathered during phase one, the systematic assessment for resilience (SAR) was developed. The SAR theoretically promotes four resilience constructs—self-control, management, engagement, and growth—and does so through five phases of assessment— assessment experience, assessment direction, assessment preparation, examiner focus, and student reflection. In addition, each assessment phase contains several practical guidelines to promote resilience. The SAR showed a high level of content and face validity. During the first track’s evaluation, most of the SAR guidelines were adhered to, and the teachers provided promising feedback. In the second track of evaluating the SAR, the implementation of the SAR in a medical school significantly improved students’ mental health paramters. Additionally, the medical teachers at the study site shared their positive experiences and reported significant student changes after implementing SAR. The current study presents a novel and holistic framework for fostering student resilience through assessment practice. The novelty of the SAR comes from its uniqueness as a resilience intervention that targets the leading cause of medical students’ mental health problems, approaching this in a systematic way, in turn providing a new horizon for the assessment process in medical education. Nevertheless, additional research is required to provide more evidence on the effectiveness of SAR guidelines addressing the wellbeing issues of tomorrow’s doctors through assessment.